Effects of certified‐organic production on supplier failures and potential income effects of supplier failures on producers: Evidence from vegetable and macadamia producers in Kenya. Issue 4 (6th August 2020) - Canwat, Vincent; Oelofse, Myles; Onakuse, Stephen; de Neergaard, Andreas
Abstract: Organic agriculture uses contracts and networks to overcome its asset‐specificity problems and to ensure compliance with its standards and norms, including environmental conservation. This study analyzed the effects of certified‐organic production on supplier failures and the potential income effects of these failures on vegetable and macadamia producers in Kenya. Using survey data and propensity score matching, the study found that organic macadamia production reduces delivery failures because its asset specificity necessitates a dedicated transport system. It also found that organic vegetable production reduces quality failures because organic consumers are often less concerned about the physical quality of organic produce. However, despite these advantages, cases of supplier failures are still rampant among both organic and nonorganic producers of macadamia and vegetables. The potential income effects of these supplier failures, especially quantity and delivery failures in macadamia, raise concerns. These problems necessitate policy interventions, especially with respect to establishing and strengthening producer organizations, which are often very instrumental in overcoming quality, quantity, and delivery failures.